Fast Food Consumption Associated with Obesity/Overweight Risk among University Female Student in Saudi Arabia - Al-Otaibi, Hala Hazam; Basuny, Amany M. (Pakistan Journal of Nutrition, 2015)
The aims of this study was to examine the pattern of fast food consumption among university students and to determine the association between fast food consumption and body weight status. A total 276 volunteer female students aged 18 to 25 years old and usually ate fast food from different college in King Faisal University, constituted the sample of the study. The prevalence of obesity/overweight was 29.7%. A total 130 (47.1%) students reported eating fast food two or more time per week and the main reasons for the consumption were lack of cooking skills. Eighty percent of the students never read the nutritional information at the fast food restaurant and only 5% of the students order healthier items always or most of the time. A significant correlation between BMI and frequency of consumption (r = 0.125; p = 0.05) was observed and the Logistic Regression model found obesity/overweight to be significantly associated with frequency of fast food consumption for students going two or more times per week (OR 3.072; 95% CI 1.107-8.523). Increase awareness about healthy choices of fast food by health education programs are recommended to promote healthy lifestyles and dietary habits among university students.